The Greater Bay Area (GBA) Development Strategy and Its Relevance to Higher Education. (March 2021) - Xie (谢爱磊), Ailei; Postiglione, Gerard A.; Huang (黄倩), Qian
Purpose: This article provides a policy review of the Greater Bay Area (GBA) development strategies and their relevance to higher education. Design/Approach/Methods: This article reviews key GBA policies adopted by the central government of China and interprets higher education cooperation policies at provincial and national levels before discussing the opportunities and challenges for higher education. Findings: The GBA Development Strategy aims to build an integrated, innovative, and internationalized economy. It presents an opportunity for universities to attract new funding opportunities as well as to prepare graduates to play a key role in the GBA. The shift toward a high-tech service-led economy would hinge upon creating an effective partnerships platform between industry and higher education institutions. To do so would require greater institutional and professional autonomy for the academic research enterprises. There is also a need for evidence-based policies by the Central and GBA regional governments. Originality/Value: The article examines the state of the relationship between GBA strategies and higher education cooperation. It can be used to guide policies to promote higher education cooperation in the GBA in a more integrated, innovative, and internationalized way.